Pigs, pork, and Heartland hogs : from wild boar to baconfest - Clampitt, Cynthia (Studies in food and gastronomy., 2018)
Pigs, Pork, andHeartland Hogs is an engaging celebration of the 12,000-year connection between humans and the world's most commonly consumed meat: pork. Throughout history, pigs shaped cultures and cuisines. Introduced into the Americas, they changed lives and, in time, helped define the Midwest, reflecting the region's diversity and abundance.